Structural and Functional Features of the Immune System of the Small Intestine (Literature Review) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the review of foreign literature on the structure and functioning of Peyer's plaques. Located in the intestinal wall, the lymphoid system associated with the mucosa ensures the development of an immune response in response to the penetration of pathogenic agents and provides immunological tolerance towards food components and commensal bacteria.